2019
DOI: 10.1155/2019/6959637
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Preoperative Serum CA125 Predicts Larger Tumor Diameter in Patients with Hepatocellular Carcinoma and Low AFP Levels

Abstract: Aim Little is known about the association between cancer antigen 125 (MUC16/CA125) concentrations and tumor diameter of patients with hepatocellular carcinoma (HCC) and low AFP levels. To fill this gap in our knowledge, we conducted a retrospective study of 427 patients with HCC with AFP ≤200 ng/mL who underwent R0 resection at our center. Methods The associations between CA125 concentrations and patients' clinicopathological characteristics were analyzed. Survival vs CA125 levels was also evaluated between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…MUC16, which encodes a protein also known as ovarian carcinoma antigen CA125, has been recognized as a crucial factor in hepatocarcinogenesis [22] and its usefulness as a diagnostic and prognostic marker has been demonstrated [23]. The present results demonstrated that the presence of MMs in MUC16 was associated with viral hepatitis, higher tumor markers and vascular invasion.…”
Section: Discussionsupporting
confidence: 53%
“…MUC16, which encodes a protein also known as ovarian carcinoma antigen CA125, has been recognized as a crucial factor in hepatocarcinogenesis [22] and its usefulness as a diagnostic and prognostic marker has been demonstrated [23]. The present results demonstrated that the presence of MMs in MUC16 was associated with viral hepatitis, higher tumor markers and vascular invasion.…”
Section: Discussionsupporting
confidence: 53%
“…Lopez et al (19) demonstrated that the CA125 cutoff values for patients with HCC were 55 U/ml in women and 12 U/ml in men. To date, the major focus of studies on CA125 levels and HCC was on the diagnosis, and only a limited number of studies have focused on the prognosis of HCC (13,15,24). In addition, the association between CA125 and prognosis in patients with HBV-related HCC has not been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CA125 provides a reference value for the prognostic evaluation of patients with various types of tumor, such as pancreatic, epithelial ovarian and lung cancer (21)(22)(23). Zhou et al (24) have reported that high preoperative serum CA125 levels predict a large tumor diameter and poor prognosis following liver resection in patients with HCC with AFP levels ≤200 ng/ml. To date, the association between CA125 levels and prognosis of patients with HBV-related HCC has not been reported in detail; although certain retrospective reports have identified an association between them (13,24), further studies are needed to confirm this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFP is one of the most widely used serological biomarkers for HCC diagnosis, with a sensitivity of 60% at a cutoff value of 20 ng/mL [ 22 ]. However, statistics show that only one-third of early-stage HCC patients can be identified using AFP detection, because the patients with significantly elevated AFP levels account for only 60%–80% of all cancer cases, and high AFP levels can also be found in non-HCC conditions [ 23 ]. PIVKA-II is a newly applied biomarker and has improved the diagnosis of HCC, with relatively high sensitivity and specificity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%